Description of Characteristics and Nutritional Status of Diabetes Melitus Patients in Banjarbaru Town - Dwi Nurhayati, Serli; Muhammad Fadhil Rahman; Herizka Rizty Emelia (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disease with a steadily increasing prevalence, particularly among the elderly and individuals with abnormal nutritional status. This study aims to describe the characteristics and nutritional status of Diabetes Mellitus patients in the working area of Banjarbaru Selatan Health Center during the period of January–March 2025. This research employed a quantitative descriptive design with a cross-sectional approach, utilizing secondary data from the medical records of Diabetes Mellitus patients recorded at the health center during the study period. Out of 367 patients, the majority were female (61%), aged over 60 years (47%), unemployed (73%), and had normal nutritional status (51%), although the prevalence of obesity was also relatively high (27%). Most DM patients were elderly women with low physical activity levels, and some were obese. Efforts for DM prevention and control should focus on health education, nutritional status monitoring, and promoting increased physical activity.